Public support for assistance for workers displaced by technology - Seth Werfel; Christopher Witko; Tobias Heinrich (Research & Politics)
Technology is expected to displace many workers in the future. The public generally supports government assistance for workers viewed as less responsible for their unemployment; thus, we ask whether individuals who lose their jobs to technology are perceived as less at fault and more deserving of government benefits, compared to those who lose their jobs to other workers. We conducted a survey experiment on a nationally representative sample in the United States, randomizing whether a hypothetical worker was replaced by technology, a foreign worker, or domestic worker, and asked questions about fault perception and support for unemployment benefits. We find that workers who lose jobs to technology (or foreign workers) are viewed as less at fault than those who lose jobs to domestic workers, and that fault attribution mediated support for unemployment benefits.